2021
DOI: 10.3390/polym13030348
|View full text |Cite
|
Sign up to set email alerts
|

Carboxymethyl Bacterial Cellulose from Nata de Coco: Effects of NaOH

Abstract: Bacterial cellulose from nata de coco was prepared from the fermentation of coconut juice with Acetobacter xylinum for 10 days at room temperature under sterile conditions. Carboxymethyl cellulose (CMC) was transformed from the bacterial cellulose from the nata de coco by carboxymethylation using different concentrations of sodium hydroxide (NaOH) and monochloroacetic acid (MCA) in an isopropyl (IPA) medium. The effects of various NaOH concentrations on the degree of substitution (DS), chemical structure, visc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 28 publications
5
33
0
Order By: Relevance
“…A maximum DS of 0.83 was obtained with 24 g/15 g cellulose of MCA. At high levels of MCA, the MCA molecules were more available and substitution in molecules of cellulose was easier [16,20]. A similar result was reported regarding the DS value of CMC from sugar beet pulp [16], banana pseudo-stems [9], Mimosa pigra peels [6], durian rinds [12], and asparagus stalk end [14].…”
Section: Degree Of Substitution (Ds) and Percent Yield Of Cmc Nsupporting
confidence: 71%
See 1 more Smart Citation
“…A maximum DS of 0.83 was obtained with 24 g/15 g cellulose of MCA. At high levels of MCA, the MCA molecules were more available and substitution in molecules of cellulose was easier [16,20]. A similar result was reported regarding the DS value of CMC from sugar beet pulp [16], banana pseudo-stems [9], Mimosa pigra peels [6], durian rinds [12], and asparagus stalk end [14].…”
Section: Degree Of Substitution (Ds) and Percent Yield Of Cmc Nsupporting
confidence: 71%
“…However, plant cellulose causes deforestation and environmental problems. Therefore, many research projects have reported that CMC can be synthesized from agricultural wastes such as sugar beet pulp [16], cavendish banana pseudo-stems [9], sago waste [17], papaya peels [18], Mimosa pigra peels [6], durian rinds [12], mulberry paper [19], asparagus stalk end [14], and bacterial cellulose [20].…”
Section: Cll-oh + Naoh → Cll−ona + H 2 Omentioning
confidence: 99%
“…For example, depending on the varying concentration of NaOH, V. Pushpamalar (2006) [141] reported a range of DS of 0.51-0.82 (for sago waste) [5]; 0.56-0.87 (for durian rind) [9]; 0.14-1.76 (for water hyacinth) [140]; 0.1-2.41 (for corn husk) [119]; and 0.15-0.93 (for African star apple seed shell) [141], respectively. A higher DS value was determined mostly against 30% NaOH [116,119,141] and negligible at 25% and 10% NaOH [5,140]. Interestingly, under or above the 30% NaOH, the DS value often declines due to low reaction rate and polymer degradation [116].…”
Section: Degree Of Substitutionmentioning
confidence: 95%
“…), and property-based applications of aqueous Na-CMC (or H-CMC). Because the high or low viscosity of the applied medium is maintained with increasing or decreasing CMC concentration, respectively; on the other hand, the viscosity property of CMC also depends on or is influenced by the source parameters (like cellulose particle size, molecular weight, and DS) and synthesis conditions (concentration of NaOH, reaction temperature, and pH of solution) of CMC from cellulose, as depicted in the Supplementary Materials (Figure S3) [10,[116][117][118][119].…”
Section: Viscositymentioning
confidence: 99%
“…The water-soluble matter (SM) of the films was determined in triplicate as described by Rachtanapun et al [22], with slight modifications. Film samples (2 cm × 2 cm) were dried at 105 • C for 24 h, kept in desiccators for 24 h, weighed at 0.2000 g initial dry weight (W i ), and then immersed in 50 mL of distilled water for 24 h at 25 • C and stirred at 68 rpm.…”
Section: Water-soluble Mattermentioning
confidence: 99%